Laparoscopic completion gastrectomy in elderly patients with remnant gastric cancer: a case series - Masaki Kaihara; Satoru Matsuda; Eisuke Booka; Fumitaka Saida; Jumpei Takashima; Hanako Kasai; Koki Mihara; Atsushi Nagashima; Tomohisa Egawa (Surgical Case Reports, 2019)
Abstract Background Open completion gastrectomy (OCG) has been selected to treat remnant gastric cancer (RGC) due to severe adhesions and difficulty recognizing anatomical orientation after primary gastrectomy. In general, elderly individuals’ physiological reserves gradually decrease. Moreover, elderly patients (EPs) often have multiple complicating factors (i.e., frailty and comorbidities), leading to more postoperative complications after abdominal surgery. Recently, several trials revealed the advantages of laparoscopic surgery for EPs with gastric cancer in early recovery. However, there are limited studies investigating the use of laparoscopic completion gastrectomy (LCG) for RGC in EPs. This study aims to assess the efficacy of LCG in EPs aged ≥ 70 years. We compared the short- and long-term outcomes of LCG with those of OCG. Case presentation Twenty-one EPs who underwent completion gastrectomy for RGC between 2007 and 2017 were enrolled and classified into two groups according to the surgical approach, namely the LCG (n = 6) and OCG (n = 15) groups. We adopted the G8 geriatric screening tool to comprehensively evaluate the EPs’ physical, mental, and social functions. Patient characteristics, clinicopathological characteristics, surgical outcomes, and survival were retrospectively reviewed and compared between groups. Results There was no significant difference in the preoperative modified G8, indicating that the EPs’ backgrounds between the groups were comparable. Of note, blood loss during surgery was significantly reduced in the LCG group [median (range); LCG, 50 ml (20.0–65.0); OCG, 465 ml (264.5–714.0); p = 0.002]. The median number of retrieved lymph nodes in the LCG and OCG groups were 7 (range 4–10) versus 3 (range 1–6), respectively. There were no statistically significant differences in postoperative hospitalization, intake of solid food, and Clavien–Dindo grade ≥ II postoperative complications. In patients with a history of gastrectomy for gastric cancer in the LCG group, operative time tended to be longer in patients who underwent D2 lymph node dissection as primary surgery. Conclusions LCG was comparable to OCG for the treatment of RGC in EPs with significantly reduced blood loss. While LCG should be selected with caution in patients who have undergone D2 lymph node dissection as primary surgery, it could be considered as a surgical procedure in EPs with RGC.